Comparative Structural Dynamics of Isoforms of Helicobacter pylori Adhesin BabA Bound to Lewis b Hexasaccharide via Multiple Replica Molecular Dynamics Simulations - Roy, Rajarshi; Jonniya, Nisha Amarnath; Sk, Md Fulbabu; Kar, Parimal (Frontiers in Molecular Biosciences, 2022)
BabA of Helicobacter pylori is the ABO blood group antigen-binding adhesin. Despite considerable diversity in the BabA sequence, it shows an extraordinary adaptation in attachment to mucosal layers. In the current study, multiple replica molecular dynamics simulations were conducted in a neutral aqueous solution to elucidate the conformational landscape of isoforms of BabA bound to Lewis b (Leb) hexasaccharide. In addition, we also investigated the underlying molecular mechanism of the BabA-glycan complexation using the MM/GBSA scheme. The conformational dynamics of Leb in the free and protein-bound states were also studied. The carbohydrate-binding site across the four isoforms was examined, and the conformational variability of several vital loops was observed. The cysteine–cysteine loops and the two diversity loops (DL1 and DL2) were identified to play an essential role in recognizing the glycan molecule. The flexible crown region of BabA was stabilized after association with Leb. The outward movement of the DL2 loop vanished upon ligand binding for the Spanish specialist strain (S381). Our study revealed that the S831 strain shows a stronger affinity to Leb than other strains due to an increased favorable intermolecular electrostatic contribution. Furthermore, we showed that the α1-2-linked fucose contributed most to the binding by forming several hydrogen bonds with key amino acids. Finally, we studied the effect of the acidic environment on the BabA-glycan complexation via constant pH MD simulations, which showed a reduction in the binding free energy in the acidic environment. Overall, our study provides a detailed understanding of the molecular mechanism of Leb recognition by four isoforms of H. pylori that may help the development of therapeutics targeted at inhibiting H. pylori adherence to the gastric mucosa.